ANALISIS KEPUASAN BELANJA ONLINE DAN KAITANNYA TERHADAP PEMBELIAN ULANG (Studi Pada Mahasiswa Perbankan Syariah Angkatan 2020 UIN Sjech M.Djamil D.jambek Bukittinggi) - Maharani, Rita; Kenedii, Jon (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research examines the impact of Online Shopping Satisfaction on Repeat Purchases among students of the 2020 class of the Sharia Banking department at UIN Sjech M. Djamil Djambek Bukittinggi. A quantitative approach was chosen for this study. In data analysis, several stages were applied: first, instrument testing, which includes validity and reliability tests; second, classical assumption testing, which involves normality tests; third, hypothesis testing, consisting of simple linear regression analysis, correlation coefficient tests, determination tests, and finally, t-tests. In this research, data processing was conducted using SPSS version 26 software. The statistical t-test analysis identified that the Online Shopping Satisfaction variable (X) has a significant effect on Repeat Purchases (Y), with a t-statistic value of 5.496, which exceeds the critical t-value of 1.991. Furthermore, the determination coefficient analysis revealed that Online Shopping Satisfaction (X) contributes 28.2% to Repeat Purchases (Y). In comparison, the remaining 71.8% is influenced by other factors not explained in this study